Diagnostic Hysteroscopy and Adenomyosis: The Case of a Uterine Cornual Cavern. A Video Article. Issue 2 (2017) - Mazzon, Ivan; Favilli, Alessandro; Grasso, Mario; Gerli, Sandro
Introduction: The aim of this study is to show a rare case of adenomyosis presented as a "cavern" which completely involves a uterine cornu. Case description: A 39-year-old nulliparous patient, with five previous laparoscopic myomectomies during which multiple myomas and adenomyomas have been removed, presented at the Arbor Vitae Centre for Endoscopic Gynaecology in Rome because of an abnormal uterine bleeding. A 6 cm myoma with multiple endometrial glands inside, located on the left uterine cornu, was enucleated during the last procedure. The ultrasound scan showed a 1 cm endometrial polyp and suspected adenomyosis reaching the serosa on the left uterine cornu. Free-anaesthesia diagnostic hysteroscopy was performed with carbon dioxide as distension medium and using a 30-degree fore-oblique rigid telescope with a diameter of 2.9 mm, covered with a single-flow examination sheath. An electronic hysteroflator was set at a flow rate of 30 mL/min and a maximum intrauterine pressure of 75 mm Hg. Multiple adenomyosis caverns that deepen into the myometrium were found on the left uterine cornu. Conclusions: Previous multiple myomectomy may seriously alter the internal uterine anatomy, especially in presence of adenomyosis. In case of presence of numerous recesses in the uterine cavity, a suspicion of adenomyosis should be considered.